2019
DOI: 10.1039/c9ra04871e
|View full text |Cite
|
Sign up to set email alerts
|

Highly reactive energetic films by pre-stressing nano-aluminum particles

Abstract: Energetic films were synthesized using stress altered nano-aluminum particles (nAl).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 28 publications
1
11
0
Order By: Relevance
“…Particle size distributions are shown in Supplementary Information , Figure S1 with the measured mean diameter and standard deviation reported in Table 1 along with the label identifier for each powder. The annealing and quenching process does not alter the size distribution and this was confirmed previously for nAl powders in Bello et al [12] and μAl powders in McCollum et al [13].…”
Section: Methodssupporting
confidence: 78%
See 1 more Smart Citation
“…Particle size distributions are shown in Supplementary Information , Figure S1 with the measured mean diameter and standard deviation reported in Table 1 along with the label identifier for each powder. The annealing and quenching process does not alter the size distribution and this was confirmed previously for nAl powders in Bello et al [12] and μAl powders in McCollum et al [13].…”
Section: Methodssupporting
confidence: 78%
“…The shell becomes delaminated from the core and is theorized to fracture more easily. The core-shell delamination in SQÀ Al is a function of Al particle size because μAl has shown 52 % core-shell interfacial surface area delamination [9] while nAl has shown 81 % core-shell interfacial surface area delamination [12]. Without support from the core, the shell more easily fractures thereby enhancing diffusion controlled reactions.…”
Section: Introductionmentioning
confidence: 99%
“…The thermal processing of Al powder, specifically its annealing followed by fast quenching had been developed by Hill et al [19]. A number of subsequent studies further demonstrated distinctly different performance of as-received (i. e., called UN, untreated) and thermally processed (i. e., called SQ, super-quenched) powders in different energetic formulations [20,21,23]. Thermal processing the powder resulted in high internal particle stress [19,23], but a link to the mechanism for performance variation remained unclear.…”
Section: Effect Of Thermal Processing Of Al Powder On the Materials R...mentioning
confidence: 99%
“…A number of subsequent studies further demonstrated distinctly different performance of as-received (i. e., called UN, untreated) and thermally processed (i. e., called SQ, super-quenched) powders in different energetic formulations [20,21,23]. Thermal processing the powder resulted in high internal particle stress [19,23], but a link to the mechanism for performance variation remained unclear. Recently, we demonstrated that thermal processing also affected surface energy which was linked to low-temperature reactivity of the powder [24,25].…”
Section: Effect Of Thermal Processing Of Al Powder On the Materials R...mentioning
confidence: 99%
“…Several studies have focused on improving the reactivity of Al nanoparticles by their microstructural alteration through induction of thermomechanical stresses. The core of the Al nanoparticles nominally exists under tensile stress at room temperature, which attains a zero-strain state when heated to ∼673 K . It has been observed that preannealing of Al nanoparticles at around ∼673 K for several minutes followed by fast quenching induces dilatational lattice strain on the core, which appears to enhance Al transport through the shell. Additionally, an investigation on aging behavior of nanothermite composites of Al with oxidizers such as CuO, Fe 2 O 3 , and Co 3 O 4 , by annealing of the mixtures at ∼473 K for 15 days, showed that the alumina shell became nonuniform in thickness . The nonuniformity in the thickness of the shell led to a higher mass transport rate of Al through the thinner regions, resulting in an unexpectedly high reactivity of the annealed nanothermite composites.…”
Section: Introductionmentioning
confidence: 99%